EVALUATION OF NEUTROPHIL-LYMPHOCYTE RATIO AND ARTERIAL STIFFNESS INDICES AMONG YOUNG PREHYPERTENSIVES: A CROSS-SECTIONAL STUDY - V, Deepika; R, Vijaya Kumar (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â  Â Objective: The aim of the present study is to evaluate the arterial stiffness indices and neutrophil-lymphocyte ratio (NLR) in young prehypertensives. Methods: This was a cross-sectional study carried as a part of the medical health check-up program conducted on 150 students joining 1st year MBBS. Based on their blood pressure (BP) recordings they were classified as normotensives and prehypertensives. Arterial stiffness indices were assessed using finger photoplethysmography, and NLR was evaluated using automated hematological analyzer. Student's t-test and Pearson's correlation were performed using SPSS version 16 and p<0.05 was considered as statistically significant. Results: Of the 150 subjects, 106 were recruited for the present study. Based on BP, they were grouped as normotensives (n=66) and prehypertensives (n=40). Arterial stiffness indices, namely, stiffness index (SI) and reflection index (RI) reported a significant increase among the prehypertensive group with p=0.003 and p=0.002, respectively. SI and RI showed a positive correlation with systolic BP, diastolic BP, heart rate, and body mass index (BMI). NLR reported a significant increase in a prehypertensive group with p=0.03 but no correlation was found between NLR and arterial stiffness indices. Conclusion: Targeting the high-risk individuals, based on increased arterial stiffness, NLR, BMI and BP, for earlier lifestyle modifications could act as a potential preventive strategy to inhibit the development of cardiovascular diseases.